Electrode reversibility of Electric Arc Furnace Slag for degradation of acid orange II / Nur Zulaikha Zainudin and Dr. Norhaslinda Nasuha - Zainudin, Nur Zulaikha; Nasuha, Norhaslinda (2020)
In this study, Electric Arc Furnace Slag (EAFS) is a type of waste was used as an electrode for degradation of acid orange II (AOII). AOII is an example of dye that produce from the textile industry. The objective EAFS and iron oxide electrode were analyzed to study the electrochemical properties specifically on the reversible reaction for the degradation of AOII using the cyclic voltammetry (CV) and investigate the current and potential of EAFS electrode. CV is mostly technique used in electrochemical process to obtain the information regarding the reaction involved such as redox reaction that occur in the process. The powdered EAFS and iron oxide mixed with resin solution before place on top of the screen-printed electrode (SPE). The dye solution, AOII mixed with 0.5M sodium chloride (NaCl) was added to the SPE. Then, the SPE was connected to the potentiostat then tested for 3 complete cycles using the software NOVA 1.10. In this work, the additional of oxidizing agent which is hydrogen peroxide was used in the dye solution. The CV analysis showed both electrodes have quasi-reversible reaction. However, EAFS electrode showed the peak to peak current ratio that could have unity by increasing the scan rate more than 60mV/s which means the reversible reaction may occur. Then, the reversible reaction occurred as the potential current for anodic and cathodic were in unity. Based on the work done, the peak current was not in similarity which resulted in quasi-reversible reaction. To conclude, the EAFS electrode had higher efficiency for degradation of AOII compared to the iron electrode as the pattern of graph showed the higher tendency towards the reversible reaction compared to the iron electrode.